Highly corrosion-resistant and photocatalytic hybrid coating on AZ31 Mg alloy via plasma electrolytic oxidation with organic-inorganic integration - Talitha Tara Thanaa; Mohammad Aadil; Alireza Askari; Arash Fattah-alhosseini; Mohammad Alkaseem; Mosab Kaseem (Journal of Magnesium and Alloys)
This study explores the development of an organic-inorganic hybrid coating to enhance the corrosion resistance and photocatalytic properties of AZ31 Mg alloy modified by plasma electrolytic oxidation (PEO). The PEO process typically generates a porous oxide layer, which can reduce corrosion protection by allowing corrosive agents to penetrate the substrate. To address this limitation, phenopyridine (PHEN) and 2-methylimidazole (2-IMD) were incorporated into the PEO surface to form a robust organic layer on the Mg alloy. Potassium hydroxide (KOH) was used to adjust the pH, improving the interaction and solubility between the organic molecules and the PEO coating. The hybrid coating exhibited unique twig-like surface structures that contributed to forming a multifunctional coating with high corrosion resistance and superior photocatalytic activity. The PEO-PHEN-2IMD sample on the Mg alloy demonstrated exceptional corrosion resistance, with the lowest corrosion current density (Icorr) of 1.92 × 10-10 A/cm², a high corrosion potential (Ecorr), and the highest top layer resistance (Rtop) of 2.57 × 106 Ω·cm², indicating excellent barrier properties. Additionally, the coating achieved complete (100%) degradation of methylene blue (MB) within 30 min under visible light. Density Functional Theory (DFT) calculations provide deeper insights into the bonding mechanisms and interaction stability between PHEN, 2-IMD, and the PEO layer on the Mg alloy and MB dye. These findings confirmed the enhanced performance of the hybrid coating in both corrosion resistance and photocatalytic applications.